PERAN LAZISMU JAWA TIMUR MEMBENTUK MASYARAKAT MANDIRI DALAM MENGHADAPI PANDEMI COVID-19 - Fauzan Karback; Muhammad Tsabat Zidni; Lama'ah Lama'ah; Laila Masruro Pimada (HUMAN FALAH: Jurnal Studi Ekonomi dan Bisnis Islam, 2020)
AbstractThis study aims to provide recommendations on productive zakat programs by Lazismu East Java from the results of the analysis of the poverty problem due to the COVID-19 pandemic with the potential possessed by Lazismu East Java. This type of research is a qualitative approach using quantitative methods so that the data information obtained through data sourced on the official website page, previous research, information that contains facts. There are three things that will be given in economic empowerment activities during the COVID-19 pandemic, namely capital, motivation, and training. Products produced in the implementation of community empowerment programs are dry food, frozen food, and cloth masks. Researchers chose the Cooperative as the seller of the finished goods that have been produced by mustahiq from the results of empowerment. Researchers choose the type of mustahiq namely poor and poor because the income level is relatively down. Researchers suggest that there be collaboration between Lazismu East Java and the community.Keywords: Lazismu East Java, Pandemic COVID-19, and Productive Zakat  AbstrakPenelitian ini bertujuan untuk memberikan rekomendasi program zakat produktif oleh Lazismu Jawa Timur dari hasil analisis masalah kemiskinan akibat pandemi COVID-19 dengan potensi yang dimiliki oleh Lazismu Jawa Timur. Jenis penelitian ini adalah pendekatan kualitatif dengan menggunakan metode kuantitatif sehingga informasi data diperoleh melalui data yang bersumber pada halaman situs web resmi, penelitian sebelumnya, informasi yang mengandung fakta. Ada tiga hal yang akan diberikan dalam kegiatan pemberdayaan ekonomi selama pandemi COVID-19, yaitu modal, motivasi, dan pelatihan. Produk yang dihasilkan dalam implementasi program pemberdayaan masyarakat adalah makanan kering, makanan beku, dan masker kain. Peneliti memilih Koperasi sebagai penjual barang jadi yang telah diproduksi oleh mustahik dari hasil pemberdayaan. Peneliti memilih jenis mustahiq yaitu miskin dan miskin karena tingkat pendapatannya relatif turun. Peneliti menyarankan agar ada kolaborasi antara Lazismu Jawa Timur dan masyarakat.Kata Kunci: Lazismu Jawa Timur, Pandemi COVID-19, dan Zakat Produktif